Revitalisasi Nasionalisme Pelajar Indonesia di Taiwan melalui Workshop Penguatan Nilai-nilai Identitas Bangsa: Penelitian - Hasanah, Nurul; Nuansa Bayu Segara; Hendri Prastiyono; Durrotun Nafisah; Muhammad Ilyas Marzuqi; Dhimas Bagus Virgiawan; Agung Stiawan; Delnabila Dwi Olivia; Arina Eliana Fitria (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Studying abroad has become a strategic option for improving the quality of human resources capable of competing amid the rapid advancement of global technology and knowledge. Taiwan, as a country experiencing significant progress in education, technology, and economic development, has become an attractive study destination for Indonesian students. However, the impacts of this phenomenon indicate a tendency toward cultural assimilation that may lead to shifts in national identity, particularly toward Westernized characteristics. This condition highlights the need to strengthen national identity values among Indonesian students studying overseas. This PKM (Community Service Program) activity aims to provide insights into national identity while reinforcing a sense of pride and nationalism in the midst of global cultural influences. The implementation methods include workshops and sharing sessions with Indonesian students regarding their experiences in dealing with cultural challenges in Taiwan. The activities were conducted in three phases: preparation, implementation, and evaluation followed by follow-up actions. The results show an increased understanding among participants regarding the importance of preserving their identity as Indonesians, as well as the emergence of a commitment to internalize national identity values.